2009
DOI: 10.5858/133.4.628
|View full text |Cite|
|
Sign up to set email alerts
|

Relation Between Red Blood Cell Distribution Width and Inflammatory Biomarkers in a Large Cohort of Unselected Outpatients

Abstract: Context.—A strong independent association has been recently observed between elevated red blood cell distribution width (RDW) and increased incidence of cardiovascular events. Objective.—To assess whether RDW is associated with plasma markers of inflammation since the mechanism(s) underlying this association remain unknown. Design.—We retrospectively analyzed results of RDW, hemoglobin, mean corpuscular volume, ferritin, high-sensitivity C-reactive protein (hsCRP), and erythrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
259
4
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 706 publications
(282 citation statements)
references
References 16 publications
9
259
4
10
Order By: Relevance
“…In the limited number of studies in our country investigating the relationship between IDA and FS (14,19) RDW is a routinely used test to define the etiology of anemia, and is an index that automatically measures the heterogeneity of erythrocytes. Moreover, RDW has been shown to be positively correlated with inflammatory markers in the presence of certain diseases (such as cardiovascular and autoimmune diseases and cancer) and can therefore be considered as a potential inflammatory marker (21). In a study by Goksugur et al (22), RDW was shown to be a simple, effective and practical marker for the differentiation of FS types, while another study has reported that RDW was not significantly helpful in the differentiation of FS types (23).…”
Section: Discussionmentioning
confidence: 99%
“…In the limited number of studies in our country investigating the relationship between IDA and FS (14,19) RDW is a routinely used test to define the etiology of anemia, and is an index that automatically measures the heterogeneity of erythrocytes. Moreover, RDW has been shown to be positively correlated with inflammatory markers in the presence of certain diseases (such as cardiovascular and autoimmune diseases and cancer) and can therefore be considered as a potential inflammatory marker (21). In a study by Goksugur et al (22), RDW was shown to be a simple, effective and practical marker for the differentiation of FS types, while another study has reported that RDW was not significantly helpful in the differentiation of FS types (23).…”
Section: Discussionmentioning
confidence: 99%
“…ESR is a well-known adverse prognostic factor in HL and is directly linked to the patient's pro-inflammatory status [45]. RDW is associated with age, comorbidities, and systemic inflammation [46,47]. All of this could suggest a potential link among neuroticism, low conscientiousness, pro-inflammation, and HL.…”
Section: Discussionmentioning
confidence: 99%
“…RDW is strongly weighted as a risk factor for sepsis in UTI patients in the present nomogram. One study indicated that (28) there is a strong, positive, and independent association between RDW and traditional biomarkers of inflammation, possibly because inflammation reduces the survival rate of red blood cells, leading to differences in red blood cell volumes, and an increase in size heterogeneity among red blood cells. Other studies have indicated that oxidative stress may lead to increases in RDW by increasing erythrocyte turnover, therefore resulting in an association between cell-size inequality and human pathology (29).…”
Section: Figure 1 |mentioning
confidence: 99%